Estrogen-mediated regulation of steroid metabolism in rat glial cells; effects on neurosteroid levels via regulation of CYP7B1-mediated catalysis. Issue 145 (January 2015) - Wicher, Grzegorz; Norlin, Maria
Highlights: CYP7B1 catalysis is quantitatively important for steroid metabolism in rat astrocytes. Estrogens suppress CYP7B1-catalyzed metabolism of several steroids in rat astrocytes. Estrogen treatment of astrocytes increases neurosteroid levels in culture medium. Suppression of CYP7B1 metabolism by estrogen is also seen in rat Schwann cells. Effects via CYP7B1 may regulate levels of neurosteroids in the CNS and PNS. Abstract: Many neuroactive steroids, including dehydroepiandrosterone (DHEA), pregnenolone, 27-hydroxycholesterol and 17β-estradiol, are known to affect development and function of the brain and nervous system. These and other steroids can undergo tissue and/or cell-specific enzymatic conversions into steroid metabolites. Carefully regulated production of steroids with various physiological effects is important for cells of the nervous system. Astrocytes express many steroidogenic enzymes and are considered important producers of brain steroids. The quantitative roles of different pathways for steroid metabolism in rat astrocytes are not clear. In the current study we examined effects of estrogens on steroid metabolism catalyzed by CYP7B1 and other enzymes in primary cultures of rat astrocytes. The CYP7B1 enzyme, which has been linked to neurodegenerative disease, is involved in the metabolism of several important neurosteroids. In the present study, we found that 7α-hydroxylation, performed by CYP7B1, is the quantitatively most important pathway for DHEA metabolism in rat astrocytes. In addition, our present experiments on catalytic steroid conversions revealed that estrogens significantly suppress the CYP7B1-catalyzed metabolism of not only DHEA but also of pregnenolone and 27-hydroxycholesterol in rat astrocytes. These novel findings point to a regulatory mechanism for control of the cellular levels of these neurosteroids via CYP7B1. Our hypothesis that estrogens can regulate neurosteroid levels via this enzymatic reaction was supported by experiments using ELISA to assay levels of DHEA and pregnenolone in the presence or absence of estrogen. Furthermore, the present results show that estrogen suppresses CYP7B1-catalyzed 7α-hydroxylation also in primary cultures of rat Schwann cells, indicating that regulation by estrogen via this enzyme may be of relevance in both the CNS and the PNS.